2012
DOI: 10.1515/cclm-2012-0272
|View full text |Cite
|
Sign up to set email alerts
|

UrineCART, a machine learning method for establishment of review rules based on UF-1000i flow cytometry and dipstick or reflectance photometer

Abstract: An algorithm based on machine learning methods for review criteria can be achieved via systematic comparison of UF-1000i flow cytometry and microscopy.Using Urine CART, our microscopic review rate can be reduced to around 30 % , while decreasing significant losses in urinalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 24 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Yuan et al exploited three classifiers based on supervised ML methods to distinguish between positive and negative urine samples. Based on a classification and regression tree (CART), the model made predictions about the test results with 95.6% overall sensitivity [20]. The results showed that ML is a valuable method for creating classifiers for urine microscopic examination rules.…”
Section: -1-literature Surveymentioning
confidence: 99%
“…Yuan et al exploited three classifiers based on supervised ML methods to distinguish between positive and negative urine samples. Based on a classification and regression tree (CART), the model made predictions about the test results with 95.6% overall sensitivity [20]. The results showed that ML is a valuable method for creating classifiers for urine microscopic examination rules.…”
Section: -1-literature Surveymentioning
confidence: 99%